Practice Teaching in Multicultural Contexts: Lessons to Training in Intercultural Teaching Skills - Escalante Rivera, Cristina (2014)
This paper presents the results of a research project entitled Teaching Exercises in Multicultural Contexts: Lessons to Training in Intercultural Teaching Skills, which was conducted during 2011-2012 by the Department of Teaching Research and Studies from the Costa Rican Ministry of Public Education (Escalante, Fernández and Gaete, 2012), in order to explore cultural diversity in classrooms and educational institutions in Costa Rica. This multicultural phenomenon has forced authorities to pay special attention to the educational services provided, particularly in elementary. In addition, it has sparked a discussion regarding the teachers’ conceptual and pedagogical void and a gap in their teaching skills to deal with student populations of different origins. Similarly, it leads to a reflection about the basic national educational curriculum. The research was conducted in 12 elementary schools from different educational districts, which have a high cultural diversity among students. Using qualitative research techniques, the opinions of principals, teachers and students regarding this topic are explored. The most important conclusion reached in this study is the absence of an intercultural pedagogy in the country’s classrooms and the need to prepare teachers in this respect.